Marxism, early Soviet sociolinguistics, and Gramsci's linguistic ideas. (November 2018) - Carlucci, Alessandro
Abstract: In the last few decades, the relationship between linguistics and Marxism has given rise to an important debate among experts on the Italian political thinker and leader Antonio Gramsci (1891–1937). The paper summarises this debate in connection with recent research on Gramsci's intellectual biography, starting from his university training in historical linguistics as well as other sources for his early views on language (Section2 ). Section3 focuses on his subsequent encounter with sociological and applied linguistics in revolutionary Russia, where Marx was an oft-cited author. This historical review sets the ground for a reappraisal of Gramsci's Prison Notebooks, written during the last part of his life (Section4 ), and of their contribution to the language sciences – which, I argue, is better understood if we reject the idea of a contrast between Gramsci's Marxism and his linguistic ideas (Section5 ). Finally, a brief concluding section recapitulates the various aspects discussed, especially the role of Marxist and non-Marxist sources in shaping Gramsci's views and relevance to today's linguists.